'MONUMEN KREWENG' 3D ANIMATION VIDEO AS A VISUAL BRANDING STRATEGY FOR JURON TOURIST VILLAGE - Marwanto, Aries Budi; Afrianto, Damar Tri; Dwi Atmaja, Nur Rahmat Ardi Chandra (Seni Media Rekam ISI Surakarta, 2021)
The development of tourist destinations in this digital era focuses on using technology to develop successful tourism recovery during the pandemic era. We use this principle to develop a tourism strategy using 3D animated videos to introduce Juron Village as a tourist village. Specifically, this study analyzes the visual strategy of a 3D animation video entitled